Succumbing Employees Threatened with Layoffs - Gus Muiid, Azwin; Saut H Hutahaean, Erik; Fahrudin, Adi (Rifa'Institute, 2023)
Introduction: The consequences of termination of employment (layoff) are not only felt by employees who experience layoffs, but the remaining employees also feel worried due to the pressure that comes and repeats until they experience depression because they feel that the pressure they receive is very heavy and then give up and surrender to the situation. Objective: This study aims to examine how much impact succumbing arising from the influence of job insecurity felt by employees who are threatened with layoffs. Method:This research uses quantitative methods with correlational studies and regression analysis. The population involved in this study is Private Airline Company X airline employees who are affected or experience the threat of layoffs as many as 121 people. Result and Discussion: The respondents obtained consisted of 49 men and 72 women. Kendall' s Tau-B correlation test produces a p value of <.001 with the conclusion that there is a significant relationship between variables with a kendall's Tau-B value of 0.446. Conclusions: There is a correlation between moderate and positive relationship between job insecurity and succumbing, with the conclusion that the higher the level of employee job insecurity, the greater the perceived succumbing.